Modeling router hotspots on network-on-chip - Junos, S. A. M. (IEEE, 2011)
A Network-on-Chip (NoC) is a new paradigm in complex System-on-Chip (SoC) designs that provides efficient on-chip communication architecture. It offers scalable communication to SoC and allows decoupling of communication and computation. In NoC, design space exploration is critical due to trade-offs among latency, area, and power consumption. Hence, analytical modeling is an important step for early NoC design. This paper presents a novel top-down approach router model, and utilizes this model for analysis mesh NoC performance measured in terms of throughput, average of queue size, efficiency, loss and waiting time. The model is used also to represent utilization of NoC infrastructure resources.